The Runoff Observation and Composition Analysis in the Niyang River Basin on the Tibetan Plateau - H. Liu; H. Liu; H. Liu; J. Liu; J. Liu; J. Liu; W. Wang; W. Wang; W. Wang; X. Min; X. Min; X. Min; et al. (Proceedings of the International Association of Hydrological Sciences, 2020)
In order to study on the hydrometric methods in the high-altitude area, and learn more about the hydrological mechanism in the Qinghai-Tibet Plateau, a series of observation research were carried out in the Niyang River watershed, a tributary of the Yarlung Zangbo River. The glacier recession and the runoff variation which conducted by the climate change asked people to study more on the plateau hydrology, where is extremely lack of the hydrological monitoring and dataset in the past due to the high altitude and the cold environment. In this study, 4 basins with the areas of 182, 216, 243, 213 km2 was equipped with different types of hydrometric instruments, so that the precipitation (rainfall and snow), water level, flow speed and the meteorological elements could be measured. In addition, the soil and water in the watershed were sampled at the altitude from 3667 to 6140 m, which could be used to analyze the runoff composition. With the equipment, the applicability of the hydrometric methods and instruments were discussed according to the monitoring situation. With the samples' analysis results (including the δD, δ18O, and the chemical components), the runoff composition characteristics were analyzed. This research is funded by the NSFC project 91647111 and 91647203, which are included in the Runoff Change and its Adaptive Management in the Major Rivers in Southwestern China Major Research Plan.